Tafsir tentang Persetaraan Laki-Laki dengan Perempuan (Trans Gender) - Nadilla Dwi Putri; Wianda Putri; Jiwa Wahyu Perdana; Jendri Jendri (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
This article examines the interpretation of the Qur'an and Islamic perspectives on gender equality, focusing on transgender issues. The study explores how Islam, through Qur'anic verses and prophetic traditions, provides guidelines on gender identity, equal rights, and human dignity. Islam views humans as inherently equal and honorable, without gender-based discrimination. However, the transgender issue, particularly involving gender transitions or non-binary identities, sparks diverse interpretations among classical and contemporary scholars. The article also reviews how Islamic law perceives gender reassignment and the social status of transgender individuals in society. By analyzing verses such as QS. Al-Hujurat [49:13], QS. An-Nisa' [4:1], and QS. At-Taubah [9:71], along with contemporary scholarly literature, this study seeks to offer a balanced and just perspective on understanding this issue, rooted in the principles of justice, compassion, and humanity in Islam.